2020
DOI: 10.7759/cureus.10565
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Mastocytosis: Case Report and Review of the Literature

Abstract: Mastocytosis is a rare infiltrative disorder characterized by mast cell proliferation within the skin and various extra-cutaneous organ systems. We report the case of a full-term neonate admitted to the neonatal intensive care unit for evaluation of diffuse skin lesions on her face, trunk and extremities. Initially, the lesions appeared to be consistent with a blueberry muffin rash. However, over a period of days the lesions became vesicular and changed in shape and number. The neonate underwent evaluation for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 15 publications
3
5
0
Order By: Relevance
“…Diagnostic markers (serum tryptase, serum and urine histamine, urine N-methylhistamine) in the present case were elevated blood tryptase, similar to cases reported by Heide et al [5], Chaudhary et al [6], Jenkinson et al [7], Mann et al [27], Walker et al [28], Duckworth et al [29], Koga et al [30], Lange et al [31], Ghiasi et al [32], Folch et al [34], and Turnbull et al [35] that reported elevated markers. However, urine N-methylhistamine was not performed in this case.…”
Section: Discussionsupporting
confidence: 86%
“…Diagnostic markers (serum tryptase, serum and urine histamine, urine N-methylhistamine) in the present case were elevated blood tryptase, similar to cases reported by Heide et al [5], Chaudhary et al [6], Jenkinson et al [7], Mann et al [27], Walker et al [28], Duckworth et al [29], Koga et al [30], Lange et al [31], Ghiasi et al [32], Folch et al [34], and Turnbull et al [35] that reported elevated markers. However, urine N-methylhistamine was not performed in this case.…”
Section: Discussionsupporting
confidence: 86%
“…Furthermore, numerous studies have shown that rubbing and scratching of the skin, sudden temperature changes (such as hot baths or exposure to heat), teething, viral infections, or vaccinations may induce blistering or provoke other MC mediator-related symptoms [ 13 , 28 , 40 , 58 , 59 ]. A brief review of case reports on DCM, published since 1962, is presented in Table 2 [ 28 , 35 , 36 , 38 , 39 , 40 , 41 , 52 , 53 , 54 , 58 , 60 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 ].…”
Section: Clinical Presentation Of Diffuse Cutaneous Mastocytosismentioning
confidence: 99%
“…Furthermore, numerous studies have shown that rubbing and scratching of the skin, sudden temperature changes (such as hot baths or exposure to heat), teething, viral infections, or vaccinations may induce blistering or provoke other MC mediator-related symptoms [13,28,40,58,59]. A brief review of case reports on DCM, published since 1962, is presented in Table 2 [28,35,36,[38][39][40][41][52][53][54]58,60,[62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80][81]. As mentioned above, the familial occurrence of DCM has also been reported [52][53][54].…”
Section: Clinical Presentation Of Diffuse Cutaneous Mastocytosismentioning
confidence: 99%
“…Mastocytosis is a heterogenous disorder characterized by accumulation of mast cells in diff erent tissues [1]. Mastocytosis may be limited to skin or it may involve bone marrow, liver, spleen and lymphatic tissue as systemic mastocytosis.…”
Section: Introductionmentioning
confidence: 99%